THE STRATEGY OF BREEDING BUSSINES GIFT TILAPIA FISH (Oreocromis Sp) IN KECAMATAN TAPIAN NAULI SIPOHOLON KABUPATEN TAPANULI UTARA PROVINSI SUMATERA UTARA - Lasnyata Silitonga; Eni Yulinda; Hazmi Arief (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACTThe research was conducted in February 2017 which in Kecamatan Tapian Nauli SipoholonKabupaten Tapanuli Utara Provinsi Sumatera Utara. This research intend to identify internal factors dan external factors thatreview the strategy of breeding bussines gift tilapia fish (Oreocromis Sp) in groupof Tapian Nauli Sipoholon. The beginning of this group was as abandoned vacantland. This idea was reviewed by one of residents in Sipoholon Sub-districtexactlyin Tapian Nauli Mr. Situmeang (chairman of the Tapian Nauli Group).This group consist of 10 members. The Tapian Nauli group cultivates tilapia gift(Oreocromis Sp) because this type of tilapia gift is more profitable, but the qualityof the Tapian Nauli Group has not been fully implemented and the strategy ofdeveloping this tilapia fish enlargement business is not optimal yet. Generallytechnical problem is the death of fish seeds after sowing in a pond. The methodused is a case study which is an approach to researching social phenomenathrough a complete and thorough analysis of individual cases and analyzed usingSWOT analysis. The results show that the Tapian Nauli Group can developrapidly because has the potential and quality that can improve tilapia products.From the strategy analysis it was found that this business interest was in theSO1 strategy with the importance of 1.50 including adequate water resources, high demand for tilapia gift because of its superiority, high demand for tilapia gift seeds, and increase in group income, the strategy is to use land by opening hatchery business.Keywords: Strategy, Gift Tilapia Fish, SWOT analysis